2022
DOI: 10.1155/2022/7254990
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking and Molecular Dynamics Simulation of Fisetin, Galangin, Hesperetin, Hesperidin, Myricetin, and Naringenin against Polymerase of Dengue Virus

Abstract: Dengue fever is a disease spread by the DENV virus through mosquitoes. This disease is dangerous because there is no specific drug, vaccine, or antiviral against the DENV virus, insisting on drug discovery for dengue fever. RNA-dependent RNA polymerase (RdRp) enzyme in DENV can be a drug target because it has an important role in the virus replication process. In this research, in silico simulations were carried out on bioflavonoid compounds, namely, Fisetin, Galangin, Hesperetin, Hesperidin, Myricetin, and Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This, together with hesperetin‐induced protection in chicken embryos against virulent BPXV, led to the conclusion that hesperetin may potentially be developed as a broad‐spectrum antiviral drug against poxviruses. Previous studies have also identified in vitro antiviral activity of hesperetin against DENV, 28 SARS‐CoV‐2, 25 YFV, 51 CHIKV, 29 ZIKV 29 Sindbis virus, 30 RSV, 31 HSV‐1, 31 and influenza virus 32 . The docking and MD simulations displayed the effect of hesperetin on the viral polymerase of CHIKV, 28 ZIKV, 28 DENV, 28 and RSV 27 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This, together with hesperetin‐induced protection in chicken embryos against virulent BPXV, led to the conclusion that hesperetin may potentially be developed as a broad‐spectrum antiviral drug against poxviruses. Previous studies have also identified in vitro antiviral activity of hesperetin against DENV, 28 SARS‐CoV‐2, 25 YFV, 51 CHIKV, 29 ZIKV 29 Sindbis virus, 30 RSV, 31 HSV‐1, 31 and influenza virus 32 . The docking and MD simulations displayed the effect of hesperetin on the viral polymerase of CHIKV, 28 ZIKV, 28 DENV, 28 and RSV 27 .…”
Section: Discussionmentioning
confidence: 90%
“…[22][23][24] Recent studies have demonstrated the antiviral activity of hesperetin against herpes simplex virus type 1 (HSV-1), poliovirus type 1, parainfluenza virus type 5, respiratory syncytial virus (RSV), influenza A virus, chikungunya virus (CHIKV), Zika virus (ZIKV), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), yellow fever virus (YFV), Sindbis virus, and dengue virus (DENV). [25][26][27][28][29][30][31][32] In this study, we extended the antiviral efficacy of hesperetin against poxviruses, besides providing insights into its potential mechanisms of action.…”
mentioning
confidence: 99%
“…Infections such as dengue could be treated using this method, according to studies at both the transmission and host levels [45]. Within 24 hours, participants in a diferent trial who routinely consumed 2 tablespoons of pawpaw leaf juice daily noticed a rise in their granulocyte count [46].…”
Section: Role Of Plant Derived Bioactive Compounds For the Management...mentioning
confidence: 99%
“…Te roots may include a variety of chemical compounds or phytochemicals with a wide range of pharmacological efects [73]. Furthermore, Licorice showed excellent docking characteristics to the protein of dengue [45,74]. It was shown that glycyrrhizin can inhibit Flavivirus procreation at a high nonlethal cytotoxic dose [75].…”
Section: Role Of Plant Derived Bioactive Compounds For the Management...mentioning
confidence: 99%
“…Tropical countries have abundant medicinal plant resources which have yet to be discovered [10][11][12]. Te binahong (Anredera cordifolia) is a plant native to tropical and subtropical South American countries and later brought to Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%